Urgensi Asbāb al-Nuzūl dalam Memahami al-Qur’an - Qosim Nursheha Dzulhadi (Universitas Darussalam Gontor, 2017)
To understand the meaning of the content of the holy Qur’an, it takes a lot of disciplines, such as; ‘Ilm’ Ira>b al-Qur’a>n, ‘Ilm Awqa>t al-Nuzu>l,’ Ilm Asba>b al-Nuzu>l, ‘Ilm Ghari>b al-Qur’a>n, and so on. ‘Ilm Asba>b al-Nuzu>l is the most urgent to be studied, because knowing the causes of the decline of a verse (nas), will greatly assist the understanding and interpretation of the intent of the verse. In addition, Moslem scholars also have very intense attention to this kind of science. In history, there are at least dozens of their books which contain titles with the word Asba>b al-Nuzu>l and the titles are not limited only to the classical Moslem scholars. Contemporary Moslem scholars such as; Abd al-Fattah al-Qadi, Muqbil al-Wadi’i, Ghazi Inayah, Hammad Abd al-Khaliq Hulwah, and so on, also adds richness of development of ‘ Ilm Asba>b al-Nuzu>l. For this reason, this paper will explore the extent of the urgency of ‘Ilm Asba>b al-Nuzu>l by citing some of the opinions of Moslem scholars such as; Imam Ibn al-’id Daqiq, Imam Ibn Taymiyah, Imam al-Suyuti, Imam al-Zarkasyi, Shaykh Abu al-Fath al-Qushayri, and Sheikh Muhammad al-Zarqani. From their explanation, it was found that ‘Ilm Asba>b al-Nuzu>l plays a key role in explaining the meaning of the verse, or eliminating a number of problems related to the study of the Qur’an, especially in vulnerable interpretation sparking different thought or opinion.